Automated Synthesis of Arabinoxylan‐Oligosaccharides Enables Characterization of Antibodies that Recognize Plant Cell Wall Glycans. Issue 15 (26th February 2015) - Schmidt, Deborah; Schuhmacher, Frank; Geissner, Andreas; Seeberger, Peter H.; Pfrengle, Fabian
Abstract Monoclonal antibodies that recognize plant cell wall glycans are used for high‐resolution imaging, providing important information about the structure and function of cell wall polysaccharides. To characterize the binding epitopes of these powerful molecular probes a library of eleven plant arabinoxylan oligosaccharides was produced by automated solid‐phase synthesis. Modular assembly of oligoarabinoxylans from few building blocks was enabled by adding (2‐naphthyl)methyl (Nap) to the toolbox of orthogonal protecting groups for solid‐phase synthesis. Conjugation‐ready oligosaccharides were obtained and the binding specificities of xylan‐directed antibodies were determined on microarrays.